Extra genital heterologous malignant mixed mullerian tumor of primary peritoneal origin - Naniwadekar M; Desai S; Ranade R; Kanetkar S (Wolters Kluwer Medknow Publications, 2009)
The case of an extragenital heterologous malignant mixed müllerian tumor (MMMT) of primary peritoneal origin occurring in a 76-year-old female is presented. A large tumor was seen between the uterus and rectosigmoid occupying the entire pelvis. The uterus, fallopian tubes and ovaries were uninvolved. The tumor was composed of carcinomatous areas showing endometrioid and serous papillary differentiation and sarcomatous areas showing cartilaginous differentiation. The extragenital primary MMMTs of the female peritoneum are thought to originate from the secondary müllerian system. This case is presented for its rarity. To the best our knowledge, this is the first case of extragenital MMMT of primary peritoneal origin in Indian literature.